2011
DOI: 10.1088/2043-6262/2/2/025010
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA of genetically modified maize by a silicon nanowire field-effect transistor

Abstract: A silicon nanowire field-effect transistor based sensor (SiNW-FET) has been proved to be the most sensitive and powerful device for bio-detection applications. In this paper, SiNWs were first fabricated by using our recently developed deposition and etching under angle technique (DEA), then used to build up the complete SiNW device based biosensor. The fabricated SiNW biosensor was used to detect DNA of genetically modified maize. As the DNA of the genetically modified maize has particular DNA sequences of 35S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…In this research, the LOD was evaluated by lowering the concentration of target DNA (10 fM), as shown in Fig 10(B) . To the best of our knowledge, the LOD of the p-type silicon nanowire sensor demonstrated in this research is lower than that demonstrated by Pengfei et al [ 20 ], Adam et al [ 21 ], Ryu et al[ 44 ] or Pham et al [ 45 ], which were 1 nM, 0.1 nM, 1 pM and 200 pM, respectively. Our results verify that this silicon nanowire sensor is feasible as a biosensor to detect an extremely low concentration target DNA without additional labeling procedures.…”
Section: Resultscontrasting
confidence: 71%
“…In this research, the LOD was evaluated by lowering the concentration of target DNA (10 fM), as shown in Fig 10(B) . To the best of our knowledge, the LOD of the p-type silicon nanowire sensor demonstrated in this research is lower than that demonstrated by Pengfei et al [ 20 ], Adam et al [ 21 ], Ryu et al[ 44 ] or Pham et al [ 45 ], which were 1 nM, 0.1 nM, 1 pM and 200 pM, respectively. Our results verify that this silicon nanowire sensor is feasible as a biosensor to detect an extremely low concentration target DNA without additional labeling procedures.…”
Section: Resultscontrasting
confidence: 71%
“…Pengfei et al (2013) showed that on the basis of back-gate controlled sensors detection sensitivity for DNA and pH value improves in the subthreshold regime, which shows that optimization of SiNW-FET operating conditions, can provide significant improvement for the limits of SiNW-FET nanosensor and making it possible for higher-accuracy chemical and biological molecules detection. Pham et al (2011) fabricated SiNW-FET device using deposition and etching under angle (DEA) technique, then used to build up the complete SiNW-based biosensor. Ryu et al (2010) proposed a new method to fabricate SiNW-based biosensor devices after embedding Au nanoparticles (NPs) on SiNW to enhance the sensitivity for label-free DNA detection.…”
Section: Silicon Nws-based Fet Biosensormentioning
confidence: 99%
“…5 ) Vapor-liquid-solid (VLS) Oxide assisted growth (OAG) Metal-assisted chemical etching Coating-catalyzed metals on silicon substrate (CVD) Coating-catalyzed metals on silicon substrate-laser ablation Si wafer-coated metal catalyst introduced with Si gas source OAG-thermal evaporation OAG-HF Electroless metal deposition-chemical etching [ 4 ] [ 5 , 6 ] [ 27 ] [ 11 , 13 , 15 ] Top–down approach (Fig. 4 ) None Electron beam lithography Nanoimprint lithography DEA technology and photolithography Photolithography-DRIE-TMAH-thermal oxidation Angled thin-film deposition-micrometer scale photolithography Lateral bridging growth [ 28 ] [ 29 ] [ 30 ] [ 31 ] [ 32 ] …”
Section: Reviewmentioning
confidence: 99%